Demand Curves for Stocks Do Slope Down: New Evidence from an Index Weights Adjustment - Kaul, Aditya; Mehrotra, Vikas; Morck, Randall (Journal of Finance, 2000)
Weights in the Toronto Stock Exchange 300 index are determined by the market values of the included stocks' public floats. In November 1996, the exchange implemented a previously announced revision of its definition of the public float. This revision, which increased the floats and the index weights of 31 stocks, conveyed no information and had no effect on the legal duties of shareholders. Affected stocks experienced statistically significant excess returns of 2.3 percent during the event week, and no price reversal occurred as trading volume returned to normal levels. These findings support downward sloping demand curves for stocks.